2021
DOI: 10.1007/s13201-021-01500-7
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of reclaimed wastewater effluent from decentralized wastewater plant for irrigation

Abstract: Decentralized wastewater plants have been proven to be cost-effective, easy to construct and operate and widely used in small ruler communities. The suitability of reclaimed wastewater for irrigation purpose was evaluated in this study based on the various water quality parameters, international water quality standards and water–irrigation water quality guideline (JS 1766). Twenty-seven samples were collected from a decentralized wastewater plant that is located in Balqa Governorate in Salt city, Jordan. Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This ratio, expressed in milliequivalents per liter (meq/L), helps in assessing soil sodicity. The presence of excessive sodium quantities can negatively impact soil structure and plant growth [62,63]. Soils with SAR values greater than 13 are generally classified as sodic [64].…”
Section: Evaluation Of Analysis Resultsmentioning
confidence: 99%
“…This ratio, expressed in milliequivalents per liter (meq/L), helps in assessing soil sodicity. The presence of excessive sodium quantities can negatively impact soil structure and plant growth [62,63]. Soils with SAR values greater than 13 are generally classified as sodic [64].…”
Section: Evaluation Of Analysis Resultsmentioning
confidence: 99%
“…The cost of pumping a cubic meter of groundwater has been calculated within the range of 80-120 penny per cubic meter (1.13-1.69). $/m 3 ) according to the depth of the water surface and the type of energy used to operate the pumps (Al-Hadidi, 2002). Table 2 shows the prices of irrigation water according to the stratum system.…”
Section: -Irrigation Sectormentioning
confidence: 99%
“…Thus, for most of the crops, it has been stated that the water used for irrigation should have an EC value in the range of 750-2250 μS/cm. In case, if the water contains higher EC values then the salinity management practices like adequate drainage and leaching should be properly implemented [19]. Moreover, some ions including calcium, sodium and magnesium could affect the sodium absorption ratio (SAR), another crucial factor for assessing the sodicity risk of groundwater for irrigation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that treated wastewater's average EC values can differ significantly. For instance, one of the studies reported EC values ranging from 781 to 2810 μS/cm, with a mean value of 1801.7 μS/cm [19]. Another study indicated that EC values in groundwater varied from 63 to 3819 μS/cm, with the majority of wells consisting of freshwater (< 1000 μS/cm) during rainy seasons [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation